(untitled) (Research, Society and Development, 2020)
Good Corporate Governance practices convert principles into objective recommendations, aligning interests with the purpose of preserving and optimizing the value of the organization, facilitating its access to resources and contributing to its longevity. Public institutions, similar to privately owned companies, have, in recent decades, sought mechanisms capable of reinventing and modernizing their management models. According to the Code of Best Corporate Governance Practices of the Brazilian Institute of Corporate Governance (IBGC), the principles and practices of good corporate governance apply to any type of organization, regardless of size, legal nature or type of control. Among these organizations, hospitals are increasingly looking for marketing innovations to serve their clients quickly and effectively, and so need the corporate knowledge of their executives or managers. The objective was to identify the improvements that Management with Governance (Corporate) provided to the Hospital das Clínicas de São Paulo. In this study we used the Case Study method with participant research. The results of the research permeated towards a standardization based on the good practices of Corporate Governance, aiming at process improvements, organizational climate, transparency and accountability of the hospital to the Government of São Paulo. The use of good practices in corporate governance in hospitals is justified because it is a management and safety instrument for all stakeholders, aims to be a tool that fosters the safety of management acts, corporate legal risk, stakeholder relations, between these and the patient. Good governance in public health presents itself as a pressing and irreversible need, professionalizing the management of the organization and providing security to business and patient health. As this is a case study, the results cannot be generalized, even though the case studied is relevant and significant.